2009
DOI: 10.1002/jso.21241
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor NPRL2 in hepatocellular carcinoma plays an important role in progression and can be served as an independent prognostic factor

Abstract: Our results suggest that NPRL2 mRNA expression has prognostic significance for the survival of patients with HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 15 publications
(13 reference statements)
1
24
0
Order By: Relevance
“…We observed a decrease in NPRL2 mRNA level in 45.45% of the colon cancer patients. Downregulation of NPRL2 has been reported for some cancers such as non-smallcell lung carcinoma (NSCLC), hepatocellular carcinoma (HCC), and esophageal squamous cell carcinoma at different frequencies (Yi-Lo et al, 2006;Otani et al, 2009;Senchenko et al, 2010). The downregulation rate in our study is similar to the levels observed in HCC and esophageal squamous cell carcinoma (ESCC), but it is lower than the rates described for NSCLC (Yi-Lo et al, 2006;Otani et al, 2009;Senchenko et al, 2010).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…We observed a decrease in NPRL2 mRNA level in 45.45% of the colon cancer patients. Downregulation of NPRL2 has been reported for some cancers such as non-smallcell lung carcinoma (NSCLC), hepatocellular carcinoma (HCC), and esophageal squamous cell carcinoma at different frequencies (Yi-Lo et al, 2006;Otani et al, 2009;Senchenko et al, 2010). The downregulation rate in our study is similar to the levels observed in HCC and esophageal squamous cell carcinoma (ESCC), but it is lower than the rates described for NSCLC (Yi-Lo et al, 2006;Otani et al, 2009;Senchenko et al, 2010).…”
Section: Discussionsupporting
confidence: 69%
“…Most of the tumors in our study group (69%) were adenocarcinomas, and NPRL2 expression was similarly downregulated in 45.5% of this subgroup. Otani et al (2009) reported similar NPRL2 expression levels in both normal liver and HCC tumor tissues. However, when they analyzed NPRL2 expression according to the clinicopathological characteristics of the patients, they revealed that low NPRL2 expression levels are correlated with shorter overall and disease-free survival in HCC patients (Otani et al, 2009).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Various mutations of Nprl2 have been detected in different tumors, including lung cancer (66) and hepatocellular carcinoma (67). Nprl2 and Depdc5 (the human homolog of Sea1) are also deregulated in ovarian cancers and glioblastomas (21,68).…”
Section: Discussionmentioning
confidence: 99%
“…More than a decade ago, Nprl2 was suggested to be a tumor suppressor (Lerman and Minna, 2000). Since then, low levels of Nprl2 expression have been detected in many cancers, including hepatocellular carcinoma (Otani et al, 2009), glioblasomas (Bar-Peled et al, 2013, as well as in lung (Anedchenko et al, 2008;Ji et al, 2002;Li et al, 2004;Ueda et al, 2006), ovarian Li et al, 2004), renal (Li et al, 2004;Tang et al, 2014), colorectal (Liu et al, 2014;Yogurtcu et al, 2012) and breast cancers (Li et al, 2004). In addition, it has been reported that Nprl2 interacts with the kinase Pdk1, a key regulator of cell proliferation and survival (Kurata et al, 2008).…”
Section: Deregulation Of Gator In Cancer and Other Diseasesmentioning
confidence: 99%